A influência da formação política do Renovabr no sucesso eleitoral de candidatos no Brasil - Santos, Marjorie Lynn Nogueira (2024)
This study examines the influence of the political training provided by RenovaBR on the electoral success of its candidates in Brazil. The main objective was to evaluate how this training impacts the candidates' ability to succeed in elections, identifying factors and components of the training that contribute to its electoral effectiveness. The methodology adopted included a literature review and a case study, combining quantitative analyses and binary logistic regression to explore the relationships between sociodemographic variables, participation in prior projects, and perceptions of RenovaBR's contribution. Additionally, a content analysis was conducted based on data from an internal RenovaBR survey applied to its students. The regression results indicated that, although RenovaBR graduates exhibit a high level of engagement in candidacies, variables such as gender, race, education level, and involvement in other projects had limited influence on electoral success. This suggests that other contextual or individual factors may be more determinant. On the other hand, the content analysis revealed that, from the students' perspective, RenovaBR's training had a significant contribution to their political trajectories. It is concluded that, although RenovaBR is effective in preparing candidates and encouraging their political participation, electoral success depends on a broader combination of factors, many of which go beyond the training received.